PROVEDENTIA ALLAH DALAM PERJUMPAAN BUDAYA MA’NENE’ DI KELURAHAN PANGALA’ DITINJAU DALAM KITAB KEJADIAN 49:29-33 - Indria Dwijayanti; Yones Teppe' Pakaulembang; Chrysnaldi Elvand Jiwels (ADISAM PUBLISHER, 2023)
When Christian faith meets local culture dynamic interactions occour. It is possible that Christian beliefs will replace the locel culture. This can be seen when Christian belief in Toraja meets Ma’Nene’ culture. This research of Ma’Nene’ culture on Christian belief in Pangala’ Toraja. By using a qualitative approach or method, it was determined that the village/district, even though it is Christian (100% Christian), in fact still maintains local culture beliefs. There is also a belief in the occult, the power of darkness. The existence of the Ma’Nene’ culture will attract people’s attention, especially in Pangala’, where the ancestral spirits will bless, heal, help and save the family. There are still Toraja Christian who still believe in the effectiveness of rituals in the Ma’Nene’ culture: However, in general, the Ma’Nene’ culture is carried out without violating the Pangala’ Christian beliefs